Dissemination of Technical Assistance Information. (Policy Papers; Policy Paper ;, 2008)
This paper sets out a framework for streamlined and strengthened procedures for the wider dissemination of technical assistance-related information ("TA Information"). On the basis of this framework, management intends to issue guidelines to the staff setting forth these new procedures.